Gene silencing H-NS paralogue StpA forms a rigid protein filament along DNA that blocks DNA accessibility - Lim, Ci Ji (Oxford University Press, 2012)
Nucleoid-associated proteins are bacterial proteins that are responsible for chromosomal DNA compaction and global gene regulation. One such protein is Escherichia coli Histone-like nucleoid structuring protein (H-NS) which functions as a global gene silencer. Whereas the DNA-binding mechanism of H-NS is well-characterized, its paralogue, StpA which is also able to silence genes is less understood. Here we show that StpA is similar to H-NS in that it is able to form a rigid filament along DNA. In contrast to H-NS, the StpA filament interacts with a naked DNA segment to cause DNA bridging which results in simultaneous stiffening and bridging of DNA. DNA accessibility is effectively blocked after the formation of StpA filament on DNA, suggesting rigid filament formation is the important step in promoting gene silencing. We also show that >1 mM magnesium promotes higher order DNA condensation, suggesting StpA may also play a role in chromosomal DNA packaging.